2009
DOI: 10.1211/ijpp.17.1.0006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perceived innovation characteristics on adoption of pharmacy-based in-house immunization services

Abstract: Appropriate strategies, particularly promoting the benefit of in-house immunization services, should be implemented. The proposed model and findings may be applicable to other pharmacy-based innovative practices or other public health initiatives. We recommend that organizational leaders, researchers and practitioners consider the impact of perceived benefit and incorporate it when they design strategies to foster adoption of innovative practices. Doing this may increase the number of adopters and also increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 52 publications
(72 reference statements)
0
33
1
Order By: Relevance
“…All four identified papers on immunisation and vaccination originated from overseas [21–24] . Although the scoping exercise did not identify any UK paper on immunisation and vaccination, there is, however, evidence [25] indicating that UK community pharmacists are providing services in this area.…”
Section: Resultsmentioning
confidence: 99%
“…All four identified papers on immunisation and vaccination originated from overseas [21–24] . Although the scoping exercise did not identify any UK paper on immunisation and vaccination, there is, however, evidence [25] indicating that UK community pharmacists are providing services in this area.…”
Section: Resultsmentioning
confidence: 99%
“…An existing body of evidence has identified several determinants of successful and sustainable pharmacy innovations 50,55,58 that can inform future interventions. Further research is needed on how to tailor pharmacy-based immunization services to match heterogeneous practice sites.…”
Section: Discussionmentioning
confidence: 99%
“…2,38,43 Factors such as participation in other public health services like HIV testing and needle exchange, and perceived benefit of PBIS were predictors of in-pharmacy immunization service adoption. 50,55,56,58,59 These factors were also associated with the decision to either outsource immunization services to other health professionals or implement inpharmacy services. 46,47 A multi-state survey indicated that a high percentage of pharmacies either lacked interest in or information about how to implement pharmacist-delivered immunization services.…”
Section: Feasibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, this theory states that, adopters (i.e., pharmacists) make choices on whether to embrace an innovation (i.e., prescribing) by examining the uncertain benefits and risks of this new innovation [7]. Diffusion of Innovations theory has been widely used in many disciplines to explore innovation in health care [8] as well as pharmacy practice [9,10]. Notably, Greenhalgh and colleagues have developed a conceptual model to describe the key determinants of diffusion, dissemination, and implementation of innovation in health service organizations [11].…”
Section: Introductionmentioning
confidence: 99%